Effect of nutrient sources, gypsum and growth regulators on growth, yield and quality of Indian mustard [Brassica juncea (L.) Czern. and Cross] under sub-humid region of Uttaranchal - Soni, Sushil; Meena, L.R.; Kumar, Sanjeev (Annals of Agricultural Research, 2016)
A study was taken to assess the effect of integrated nutrient management, soil amendment andgrowth regulator on performance of Indian mustard (Brassica juncea). The inorganic sources ofnutrient supplied significantly improved growth and yield parameters, seed yield and qualityparameters of mustard along with the total uptake of N, P and S. The economic returns wereobtained higher when only inorganic sources of nutrients were supplied as compared to othersources of nutrients supplied like FYM (farm yard manure) and poultry manure. Gypsum use inmustard crop resulted in significant improvement in growth and yield parameters, stover, seedand biological yield. The total uptake of N, P and S were reported higher when 50% was appliedas gypsum at sowing and 50% at 35 DAS (days after sowing). Economic returns and benefit: costratio was higher where gypsum applied twice. Application of the growth promoter, thiourea(1000 ppm) also resulted in enhanced yield attributes, stover and seed yield of mustard.